1990
DOI: 10.1227/00006123-199006000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms of the Intracavernous Carotid Artery: Natural History and Indications for Treatment

Abstract: Of 37 patients with 44 intracavernous carotid artery aneurysms (ICCAAns) diagnosed between 1976 and 1988. patients with 20 aneurysms were followed without treatment for 5 months to 13 years (median, 2.4 years). Ten of the 20 ICCAAns were asymptomatic at diagnosis, and 10 were symptomatic. Three of the asymptomatic ICCAAns were symptomatic at follow-up. One of these required clipping because of a progressing cavernous sinus syndrome; the other 2 were minimally symptomatic and have not required treatment. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(90 citation statements)
references
References 0 publications
0
85
0
5
Order By: Relevance
“…Considering our patients been submitted to conservative treatment, it could be verified a relapsing and fluctuating course of pain symptoms and a progressive impairment of cranial nerves' function, determining a poor neurological outcome till the spontaneous occlusion of ICA 27 , when the pain scenario, determined by headache, hemifacial pain and retrobulbar pain, was improved or extinguished in all cases.…”
Section: Casesmentioning
confidence: 73%
See 2 more Smart Citations
“…Considering our patients been submitted to conservative treatment, it could be verified a relapsing and fluctuating course of pain symptoms and a progressive impairment of cranial nerves' function, determining a poor neurological outcome till the spontaneous occlusion of ICA 27 , when the pain scenario, determined by headache, hemifacial pain and retrobulbar pain, was improved or extinguished in all cases.…”
Section: Casesmentioning
confidence: 73%
“…Most clinical investigators have found an increasing risk of thrombosis with an increasing degree of stenosis [14][15][16][17][18][19] and preceded by rupture of atherosclerotic plaques 20,21 , but observations concerning plaque ulcerations [12][13][14][15][16] and intraplaque hemorrhages 22,23 have been more uncertain and controversial. The occlusion of ICA can be a dangerous complication to patients without a patent collateral circulation [24][25][26][27] , manifested as an ischemic scenario, with a devastating cerebrovascular accident, or results in spontaneous therapeutic with a patent collateral circulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Grande número dessas lesões permanece assintomática, e HSA se torna uma preocupação somente quando o aneurisma ultrapassa o anel dural distal da carótida, projetandose para o espaço subaracnóideo intradural 3,5,11 . Em 2 estudos, totalizando 90 pacientes, o risco de HSA foi de apenas 0,4% por paciente-ano 4,12 . Mais freqüen-temente, a ruptura desses aneurismas leva a uma fís-tula carótido-cavernosa direta 11,13 .…”
Section: Discussionunclassified
“…São tratados os aneurismas intracavernosos que se apresentam com ruptura aguda, compressão de nervos cranianos, episódios tromboembóli-cos ou, nos pacientes assintomáticos, quando o aneurisma se estende ao espaço subaracnóideo extracavernoso, elevando o risco de sangramento [2][3][4][5][11][12][13]24 .…”
Section: Discussionunclassified